Heme on innate immunity and inflammation - Dutra, Fabianno F.; Bozza, Marcelo T. (Frontiers in Pharmacology, 2014)
Heme is an essential molecule expressed ubiquitously all through our tissues. Heme plays major functions in cellular physiology and metabolism as the prostetic group of diverse proteins. Once released from cells and from hemeproteins free heme causes oxidative damage and inflammation, thus acting as a prototypic damage-associated molecular pattern. In this context, free heme is a critical component of the pathological process of sterile and infectious hemolytic conditions including malaria, hemolytic anemias, ischemia-reperfusion and hemorrhage. The plasma scavanger proteins hemopexin and albumin reduce heme toxicity and are responsible for transporting free heme to intracellular compartments where it is catabolized by heme-oxygenase enzymes. Upon hemolysis or severe cellular damage the serum capacity to scavange heme may saturate and increase free heme to sufficient amounts to cause tissue damage in various organs. The mechanism by which heme causes reactive oxygen generation, activation of cells of the innate immune system and cell death are not fully understood. Although heme can directly promote lipid peroxidation by its iron atom, heme can also induce ROS generation and production of inflammatory mediators through the activation of selective signaling pathways. Heme activates innate immune cells such as macrophages and neutrophils through activation of innate immune receptors. The importance of these events has been demonstrated in infectious and non-infectious diseases models. In this review we will discuss the mechanisms behind heme-induced citotoxicity and inflammation and the consequences of these events on different tissues and diseases.